Implementasi Jaminan Mutu Pendidikan Berbasis Perencanaan, Pelaksanaan, Evaluasi, dan Kepuasan Stakeholder di SD Negeri Sepang - Novi Puspa Mandiri; Andriani Andriani; Mutoharoh Mutoharoh (Journal of Innovative and Creativity, 2025)
This study aims to analyze the implementation of educational quality assurance based on four main variables: quality planning, quality implementation, quality evaluation, and stakeholder satisfaction. The research method used is quantitative with a survey approach involving 21 teachers and principals in the Sd Negeri Sepang. The results show that all four variables contribute significantly to the improvement of education quality. Systematic planning, consistent program implementation, periodic evaluation, and stakeholder satisfaction levels serve as indicators of success in building a quality culture within the educational environment. These findings emphasize the importance of integrating the four factors to achieve high-quality and sustainable education.